The Difference of Mathematics Learning Achievement between Ipad For Learning Multimedia Learning and Conventional Learning Media in Junior High School Students - Tsurayya Syarif Zain; Saifuddin Azwar (Faculty of Psychology, Universitas Gadjah Mada, 2018)
This research includes gender as moderator as well as the intelligence and motivation of learning as the covariance of learning achievement. This research design is causal-comparative by comparing mathematics learning achievement between learning with iPad and conventional media. The overall research’s subjects are 128 students. The result shows that there are differences in learning achievement between multimedia learning iPad for Learning and conventional learning media (F=48,698, p<0,05). Students who use iPad media have an average mathematics learning achievement higher than a student in conventional learning media. In this research, the interaction between genders and learning media on mathematics learning achievement proved to be low (F=0,318, p>0,05).